2018
DOI: 10.1111/aor.13292
|View full text |Cite
|
Sign up to set email alerts
|

On the Accuracy of Hemolysis Models in Couette‐Type Blood Shearing Devices

Abstract: Hemolysis is one of the most challenging issues faced by blood contacting devices. Empirical hemolysis models often relate hemolysis to shear stress and exposure time. These models were generally derived from the experimental results of Couette‐type blood shearing devices, with assumption of uniform exposure time and shear stress. This assumption is not strictly valid since neither exposure time nor shear stress is uniform. Hence, this study evaluated the influence of the nonuniform exposure time and rotor ecc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…2024 A common approach to consider turbulent effect on hemolysis is to formulate effective stress τeff using viscous stress together with Reynolds stress. 2528 However, it has been shown that the Reynolds stress is an inaccurate indicator of turbulent effects on hemolysis, 2933 and tends to overpredict the level of hemolysis. 24 Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…2024 A common approach to consider turbulent effect on hemolysis is to formulate effective stress τeff using viscous stress together with Reynolds stress. 2528 However, it has been shown that the Reynolds stress is an inaccurate indicator of turbulent effects on hemolysis, 2933 and tends to overpredict the level of hemolysis. 24 Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Goldsmith and Turitto 6 have determined these deviations in extensive comparative tests. Wu et al 26 were able to show that the critical limit of shear stresses determined with a frequently used Couette viscometer is only of limited significance for the occurrence of haemolysis. Beissinger and Laugel 27 were also able to demonstrate that the haemolysis level increases when the erythrocytes get into contact with foreign materials, regardless of the shear rate present.…”
Section: Resistance Of Erythrocytesmentioning
confidence: 99%
“…Peng Wu et al of Soochow University, Suzhou, Jiangsu, China, investigated the accuracy of hemolysis models in Couette‐type blood shearing devices. The study evaluated the influence of the nonuniform exposure time and rotor eccentricity or run‐out on the accuracy of power‐law hemolysis models, using both theoretical and CFD analysis.…”
Section: Bioengineering Biocompatibility and Biomaterialsmentioning
confidence: 99%